Development of time compressed sentence test in Bengali (TCST-B) - Biswas, Sushmita; Chatterjee, Indranil; Dutta, Palash; Narayanan, Shalini S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Auditory processing of speech involves sound localization, auditory discrimination, and auditory pattern recognition, audition of temporal aspects, auditory performance in competing acoustic signals, and auditory performance with degraded acoustic signals. Time compressed sentence test is mono aural low redundancy test which helps to identify person with APD as well as neurological deficit accompanying cortical and subcortical lesion. The purpose of the present study was to develop Time Compressed Sentence Test in Bengali and establish normative data on young adults along with investigating the effect of ear, gender, reliability and the level of compression of time compressed sentence in Bengali. Methods: 50 sentences were developed and compressed with 100% intelligibility. 100 young adults, native Bengali speaker (50male, 50 female) having normal hearing were selected for the study. The task involved repetition of monotically presented Time Compressed Sentences. The compression levels used in the present study were 0%, 40%, 50% 60% and 70%. The compressed material was administered three times (baseline, after 15 min break and after 1 week) to measure test-retest reliability. Results: Statistical analysis revealed speech identification score (SIS) decreased with increase in compression level. There was no significant gender effect or ear difference on performance. The reliability is good for 40%, 50%, 60% and acceptable for 70% compression. Conclusions: The study provides the normative values of Time compressed sentence test in Bengali for young adults. Understanding the effects of the temporally degraded stimulus in Bengali will help in better utilization of the test in clinical population.